A Study on Consumer Recycling Behaviour on Solid Waste in Nilai - Ng, Hou Hong; Tan, Ban Peng (INTI International University, 2018)
Solid Waste Management has been recognized as one of the challenges for Malaysia which the landfill method of waste disposal is no longer appropriate. Increase in waste generation, inadequately managed and uncontrolled dumpsites are all indicator of the poor waste management becoming one of the nation’s biggest issues to date. Around the world, solid waste management reveals an environmental consciousness, which has risen among the societies of environmental of environmental awareness and advocacy of environmental issues and concerns among the public. This paper explores the factor influence the recycling intention behaviour in Nilai. The design of this study is quantitative research whereby a set of hypotheses are devised and data is collected from a sample using a self-administrated questionnaire to test the proposed model and data collected from 150 questionnaires were analyzed. The findings indicate the need for a different recycling strategy, creating environmental awareness, and improving educational systems to enhance the recycling rate in Nilai.